On the dynamics of the ultra-fast rotating cantilever orthotropic piezoelectric nanodisk based on nonlocal strain gradient theory. (1st January 2021) - Al-Furjan, M.S.H.; Dehini, Reza; Khorami, Majid; Habibi, Mostafa; won Jung, Dong
Abstract: In this article, amplitude, and vibrational characteristics of a rotating orthotropic piezoelectric nanodisk are presented. The centrifugal and Coriolis effects due to the rotation are considered. The strains and stresses can be determined via the higher-order shear deformable theory (HSDT). For accessing to size effects, the nonlocal strain gradient theory (NSGT) is used for obtaining the correct results. The boundary conditions are derived through governing equations of the orthotropic piezoelectric rotating nanodisk using an energy method known as Hamilton's principle and finally are solved using the generalized differential quadrature method (GDQM). The results created from a finite element simulation illustrates a close agreement with the semi-numerical method results. Vibration characteristics of the spinning nanodisk with various boundary conditions are described based on the curves drawn by Matlab software. The outcomes show that the applied voltage, angular velocity, length scale, and nonlocal parameters, and geometrically properties of piezoelectric nanodisk have a considerable impact on the amplitude, and vibration behavior of a piezoelectric rotating cantilever nanodisk.